2021
DOI: 10.1136/bmjopen-2021-055392
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of relapse in MOG antibody associated disease: a cohort study

Abstract: ObjectiveTo identify factors predictive of relapse risk and disability in myelin oligodendrocyte glycoprotein associated disease (MOGAD).SettingPatients were seen by the neuromyelitis optica spectrum disorders (NMOSD) service in Liverpool, UK, a national referral centre for adult patients with MOGAD, NMOSD and related conditions.ParticipantsPatients with MOGAD=76 from England, Northern Ireland and Scotland were included in this cohort study.ResultsRelapsing disease was observed in 55% (42/76) of cases. Steroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 14 publications
0
27
0
6
Order By: Relevance
“…First, we identified significant publication bias towards favourable outcomes after RTX therapy; however, whether or not this observation is driven by true unequivocal efficacy cannot be determined without randomised-control trials. Second, the population reported here might be not representative of patients with MOGAD in terms of proportion of relapsing patients (75% against less than 50% in the literature) 8 74 75. Third, a short follow-up after RTX is reported in a consistent number of studies analysed (8/32, 25%), although the meta-regression found no significant association between follow-up duration and effect size.…”
Section: Discussionmentioning
confidence: 74%
“…First, we identified significant publication bias towards favourable outcomes after RTX therapy; however, whether or not this observation is driven by true unequivocal efficacy cannot be determined without randomised-control trials. Second, the population reported here might be not representative of patients with MOGAD in terms of proportion of relapsing patients (75% against less than 50% in the literature) 8 74 75. Third, a short follow-up after RTX is reported in a consistent number of studies analysed (8/32, 25%), although the meta-regression found no significant association between follow-up duration and effect size.…”
Section: Discussionmentioning
confidence: 74%
“…6,7,11,[14][15][16][17] The persistence of positive MOG antibodies at follow-up has been repeatedly, although not invariably, reported to be associated with higher risk of a relapsing disease course. 2,4,8,11,[14][15][16][18][19][20][21][22] However, current data do not allow a proper prediction of disease course or final outcome at MOGAD onset. 6,17,20,21,[23][24][25][26] In this Italian multicenter cohort of pediatric MOGAD, we strove to identify early clinical-paraclinical factors at disease onset associated with subsequent relapse and final outcome, with particular focus on modifiable factors such as treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Factors at first event independently associated with lower risk of relapsing disease course were immunotherapy <7 days from onset (6.7-fold reduced odds of relapsing course, OR 0.15, 95% CI 0.03-0.61, p = 0.009), corticosteroid treatment for ≥5 weeks (6.7-fold reduced odds of relapse, OR 0.15, 95% CI 0.03-0.80, p = 0.026), and abnormal optic nerves on onset MRI (12.5-fold reduced odds of relapse, OR 0.08, 95% CI 0.01-0.50, p = 0.007). 21.1% (15/71) had EDSS ≥ 1 at final follow-up. Patients with a relapsing course had a higher proportion of final EDSS ≥ 1 (37.5%, 9/24) than children with monophasic disease (12.8%, 5/39) (p = 0.022, univariate analysis).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Male patients with myelitis experienced a lower relapse risk. Other predictors include prolonged steroid treatment and the MOG-antibody negative seroconversion [ 13 ]. Among the seven MOG-IgG–positive patients with cranial neuropathies in this review, two had a relapsing disease course both with ON, and the other five remained monophasic.…”
Section: Discussionmentioning
confidence: 99%